The Effect of Variation Percentage Alkalization (NaOH) On the Mechanical Properties Analysis and Water Absorption Behaviour in Biocomposite with Cassava Rubber Starch - Nevada. J. M. Nanulaitta (Jurusan Teknik Mesin, 2023)
Composites made using natural ingredients namely sago fiber and cassava rubber starch as the matrix. This composite making is expected to get good bending strength, impact strength and water absorption rate. Composites are made using the hand lay-up method with a variation of the matrix and the variation of the volume fraction of sago pith fibers is 50%: 50% and 70%: 30% using NaOH liquid and distilled water in the alkali process with a percentage ratio of 0%, 5%, 10%, 15% and 20%. soaking time in NaOH liquid for 120 minutes. The results of this study were found to be the best impact value on composites with 50%: 50% fiber volume variation with 15% alkaline NaOH liquid process, the highest value on the energy absorbed by the composite was 7.5479 (J) with an impact strength of 0.0755 (J/mm2) at a variation of 70%: 30% the highest absorption energy is 5,7430 (J) while the impact strength is 0.0574 (J/ mm2) at 15% NaOH liquid percentage. The highest bending strength is 226.035 MPa at 50%: 50% volume fraction variation with 15% NaOH liquid percentage, 70%: 30% fiber volume fraction variation with the highest value 206,199 MPa at 15% NaOH liquid percentage. The best water absorption rate is at 8 , 82% that occurs in the variation of 50%: 50% fiber volume fraction with 15% percentage of the alkaline process NaOH and 9.16% in the variation of 70% fiber volume fraction: 30% fiber with 15% NaOH liquid in the alkalization process Keywords : Sago Pith Fiber, Cassava Rubber Starch, NaOH, Hand Lay Up Method, Bending Strength, Impact Strength and Water Absorption Rate